Effects of Regular Physical Activity on the Visual Analyzer and the General Condition of Children and Adolescents - O. V. Yurova; D. V. Andzhelova; A. A. Chayka (Oftalʹmologiâ)
Purpose. to study the effect of physical exertion on the visual analyzer and the general functional state in children and adolescents who regularly engage in sports. Material and Methods. The study was conducted in a group of 600 children and adolescents aged from 8 to 17 years who were divided into two groups of 300 people: the I group — “athletes” (regularly engaged in sports), the second group — “schoolchildren” (those engaged in sports less than 3 hours per week). Each group was divided into two subgroups of 150 people — “emmetrops” and “myopes”. The parameters of visual acuity, axial eye length, indices of regional eye hemodynamics were evaluated. Results. After 12 months, the group “athletes” showed a statistically significant decrease in refraction on average by 0.14 ± 0.18 on the background of stable visual acuity. In the group “schoolchildren” there was a significant reduction in visual acuity without correction by 0.06 ± 0.19 (p = 0.004) and refractive indices by 0.35 ± 0.61 (p < 0.001) on the average. After 12 months, among the emmetrops, myopia was diagnosed in 6 % of cases in the “athletes” group and 10 % in the “schoolchildren” group. Among the “myopes” in both groups there was a significant increase in the body mass index and the number of persons with impaired functional state of the musculoskeletal system in the form of a violation of posture and shape of the foot in comparison with the “emmetrops”. Сonclusion. Regular physical activity can be considered as one of the factors preventing the development and progression of myopia, and functional disorders of the musculoskeletal system in the form of violation of posture and shape of the foot and excessive body weight — as possible risk factors for the development of myopia.